Use of linked population data to apply Indigenous identity definitions in official health statistics and estimate survival inequity: a case study in New Zealand using gastric cancer cases - Davie, Gabrielle; Satherley, Nicole; Graaf, Brandon de; Gibb, Sheree; Teng, Andrea; Deen, Frederieke Petrovic-van der; Sporle, Andrew (International Journal of Population Data Science, 2026)
Despite ethnicity and descent both being officially recognised identity definitions for the Indigenous Māori population of New Zealand (NZ), official health statistics are usually reported by Māori ethnicity as health collections do not record descent. The first part of this study explored the potential of linked administrative data to describe health outcomes by Māori descent using gastric (stomach) cancer (GC) cases. For GC registrations in NZ’s Cancer Registry, data linkage was used to obtain information on Māori descent from Censuses, birth and death records. From 1995–2021, NZ had 10,575 GC registrations, of which Māori descent information was sourced for 81.8%. Of these,18.6% were identified as being of Māori descent vs 17.3% identified as Māori by ethnicity. Missing Māori descent data was lower for GC registrations from 2012. In part 2, changes in GC survival over two decades were examined among Māori and non-Māori (as defined by ethnicity). For those with GC diagnoses within 2002-2021, mortality risk (GC-specific; 1-year) was higher for Māori compared to non-Māori, although age-standardised Māori:non-Māori mortality rate ratios indicated less disparity in more recent years. Higher risk of mortality from gastric cancer for Māori compared to non-Māori was most pronounced for those aged 45–64 years. In conclusion, 1) the classification of cancer registrations by Māori descent for health outcome reporting may be feasible for more recent years, and 2) although ethnic inequity in gastric cancer mortality was observed in all 5-year time periods, this disparity appeared smaller in more recent years.